2006
DOI: 10.1007/s00345-006-0062-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipid levels in benign prostatic hyperplasia

Abstract: The relationship between serum lipid levels and measures of benign prostatic hyperplasia was investigated. The study was community based. All the participants had undergone a urological investigation which included International Prostate Symptom Score (I-PSS) and Quality of Life Score (QoL), serum lipid concentrations and determination of prostate volume with transrectal ultrasonography. Body mass index was calculated with the formula of weight (kg)/surface area (m(2)) respectively. Men were considered obese i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…For example a cross‐sectional Austrian population‐based study (N = 939) reported no association between BMI and IPSS [50]. A Turkish study (N = 286) found no relationship between serum lipids and IPSS [51]. Finally, a large‐scale population‐based study (N = 2797) from the united States, demonstrated that current BMI is unrelated to LUTS or to the history of prostatic surgery for LUTS [32].…”
Section: Discussionmentioning
confidence: 99%
“…For example a cross‐sectional Austrian population‐based study (N = 939) reported no association between BMI and IPSS [50]. A Turkish study (N = 286) found no relationship between serum lipids and IPSS [51]. Finally, a large‐scale population‐based study (N = 2797) from the united States, demonstrated that current BMI is unrelated to LUTS or to the history of prostatic surgery for LUTS [32].…”
Section: Discussionmentioning
confidence: 99%
“…Hammarsten et al found in a cohort of Swedish men with BPH that lower HDL cholesterol, higher LDL cholesterol, and higher triglycerides were associated with increased prostate volume (Hammarsten et al, 1998). While in a case control study, Indian men undergoing BPH surgery were more likely to have lower HDL and higher LDL cholesterol compared to controls (Nandeesha et al, 2006); there was no association of patient-reported hyperlipidemia with histological BPH in a case-control analysis on Italian men (Zucchtto et al, 2005) and no association of serum lipids or lipoproteins with International Prostate Symptom Score or prostate volume in a cohort of Turkish men (Lekili et al, 2006). Similarly, no association of serum lipids or lipoproteins was found with ICD-9 coded BPH diagnosis in a cohort of U.S. Air Force Veterans (Gupta et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…17 However, in a cohort of community dwelling Turkish men there were no significant associations of serum lipids with BPH or LUTS. 21 Similarly in the case-control Hypertension. Lastly, formal criteria for metabolic syndrome also include hypertension.…”
Section: Obesitymentioning
confidence: 96%